2016
DOI: 10.1021/acsami.6b04375
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Nitride Hydrolysis Enabled by Hydroxyl-Mediated Surface Proton Hopping

Abstract: Aluminum nitride (AlN) is used extensively in the semiconductor industry as a high-thermal-conductivity insulator, but its manufacture is encumbered by a tendency to degrade in the presence of water. The propensity for AlN to hydrolyze has led to its consideration as a redox material for solar thermochemical ammonia (NH3) synthesis applications where AlN would be intentionally hydrolyzed to produce NH3 and aluminum oxide (Al2O3), which could be subsequently reduced in nitrogen (N2) to reform AlN and reinitiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…It is also found that these reactions continue even after the end of the initial hydrogen transfer. [23,24,25]The same mechanism is observed in our simulations. A single H-transfer from the LAH reducing agent was able to initiate a continuous insertion of additional Al's that eventually lead to the growth of a larger aluminum complex.…”
Section: Introductionsupporting
confidence: 88%
“…It is also found that these reactions continue even after the end of the initial hydrogen transfer. [23,24,25]The same mechanism is observed in our simulations. A single H-transfer from the LAH reducing agent was able to initiate a continuous insertion of additional Al's that eventually lead to the growth of a larger aluminum complex.…”
Section: Introductionsupporting
confidence: 88%
“…Two additional challenges to this reaction have the opposite dependence on temperature. The kinetics of hydrolysis are known to be slow and alleviated by increasing the temperature. , However, NH 3 is thermodynamically favored to decompose into N 2 + H 2 with decreasing Δ G r (increased driving force for decomposition) as temperature increases, requiring the fast capture and quenching of the liberated NH 3 . Although the thermodynamic conversion of nitride to oxide by steam exposure is thermodynamically favorable for ∼600 binary redox pairs, these additional kinetic and nonequilibrium challenges will further restrict the number of truly viable pairs for this step.…”
Section: Resultsmentioning
confidence: 99%
“…Along with thermodynamics, the kinetics of each reaction in STAS are critical to the viability of the NH 3 synthesis process, especially for reactions involving nitrogen. The corrosion of metal nitrides by H 2 O is a kinetically limited process for many nitrides below 1200 K, primarily associated with the need to break metal–nitrogen bonds that can have significant covalent character. ,, Similarly, the reduction of N 2 for metal nitride synthesis requires the activation and cleavage of the triply bonded N 2 molecule, which also poses a significant kinetic challenge. The difficulty in reducing N 2 can result in metals becoming only partially nitridated, limiting the NH 3 yield that can be achieved on a per cycle basis, as this quantity is directly linked with the amount N 2 that can be fixed to the metal.…”
Section: Resultsmentioning
confidence: 99%
“…AlN degrades in water, forming Al 2 O 3 that dissolves into the AlN lattice to produce vacancies on aluminum sites (𝑉 ′′′ 𝐴𝑙 ) [7][8][9][10] :…”
Section: Introductionmentioning
confidence: 99%
“…AlN has many desirable properties, but it is expensive to produce due to the high sintering temperatures required to reach near‐theoretical density and reactivity with water. AlN degrades in water, forming Al 2 O 3 that dissolves into the AlN lattice to produce vacancies on aluminum sites (VAl$V_{Al}^{^{\prime\prime\prime}}$) 7–10 : 2AlN+3H2normalOnormalAl2O3+2NH3\begin{equation}2{\rm{AlN}} + 3{{\rm{H}}_2}{\rm{O}} \to {\rm{A}}{{\rm{l}}_2}{{\rm{O}}_3} + 2N{H_3}\end{equation} normalAl2O3AlN2normalAlAl+3ON·+VAl\begin{equation}{\rm{A}}{{\rm{l}}_2}{{\rm{O}}_3}\mathop \to \limits^{{\rm{AlN}}} 2{\rm{A}}{{\rm{l}}_{{\rm{Al}}}} + 3O_N^ \cdot + V_{Al}^{^{\prime\prime\prime}}\end{equation}…”
Section: Introductionmentioning
confidence: 99%